Effect of management commitment to internal marketing on employee work attitude. (February 2015) - To, W.M.; Martin, E.F.; Yu, Billy T.W.
Highlights: Management commitment drives the internal service-profit chain. Management commitment to internal marketing affects employee work attitude. Hotel managers must effectively utilize informal channel of communication. Abstract: The present study examines the effect of management commitment to internal marketing on employee work attitude through internal marketing practices. Data were collected from 201 full-time employees of four-star and above hotels in Macao SAR, China. The results of structural equation modeling showed that management commitment to internal marketing related to internal marketing practices including formal and informal internal communications, while formal internal communication facilitated informal internal communication. Moreover, management commitment to internal marketing and informal internal communication affected employee work attitude. The current study contributes to a deeper understanding of the internal service-profit chain.